Storage tolerance and aging-resistance of ultradried safflower seeds - HU Jia-su; ZENG Guang-Wen (浙江大学学报. 农业与生命科学版, 2000)
Storage tolerance and aging resistance of seeds were investigated with safflower seed rich in linolic acid. After storage at room-temperature, seed viability, seed vigor, activity of dehydrogenase, catalase (CAT), superoxide dismutase (SOD) were determinied. The results showed that ultradried seed became more tolerant, compaired to non-ultradried seed under storage at room-temperature. No significant change can be found either in germination rate or seed vigor after storage at room-temperature for three years. The active-oxygen-scavenging system and reserve materials were retained well during storage in ultradried state.